2020
DOI: 10.1177/0258042x20939026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inter-organizational Justice on Dimensions of Organizational Citizenship Behaviours: A Study on Kuwait Ministries’ Employees

Abstract: The aim of this article is to model the relationships between three different dimensions of inter-organizational justice (procedural, interactional and distributive) and their influence on five dimensions of organizational citizenship behaviour (OCB) (altruism, sportsmanship, conscientiousness, courtesy and civic virtue) in public sector organizations. The partial least square (PLS) path method was used to explore the nature of the relationships. The survey was self-administered to 573 employees working in nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Prior studies explored several intervening variables between OJ and OCB, such as organizational commitment ( Donglong et al., 2020 ; Jehanzeb and Mohanty, 2019 ), organizational trust ( Ullah et al., 2021 ), job satisfaction ( Junru and Huang, 2019 ; Khan et al., 2020 ), job involvement ( Sujono et al., 2020 ), psychological ownership ( Jnaneswar and Ranjit, 2021 ), and leader-member exchange ( Hasyim and Palupiningdyah, 2021 ; Sheeraz et al., 2020 ). However, there is still a call to uncover the “black box” remaining in the OJ—OCB relation ( Ambrose et al., 2021 ; Rana et al., 2018 ; Zayed et al., 2020 ). Considering the role of OJ on employee attitude and behavior, very few studies have explored the mediating role of work engagement (WE), a favourable employee attitude, in the association between organisational justice and OCB across the sectors ( Hassan et al., 2014 ; Yanthi and Rahyuda, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies explored several intervening variables between OJ and OCB, such as organizational commitment ( Donglong et al., 2020 ; Jehanzeb and Mohanty, 2019 ), organizational trust ( Ullah et al., 2021 ), job satisfaction ( Junru and Huang, 2019 ; Khan et al., 2020 ), job involvement ( Sujono et al., 2020 ), psychological ownership ( Jnaneswar and Ranjit, 2021 ), and leader-member exchange ( Hasyim and Palupiningdyah, 2021 ; Sheeraz et al., 2020 ). However, there is still a call to uncover the “black box” remaining in the OJ—OCB relation ( Ambrose et al., 2021 ; Rana et al., 2018 ; Zayed et al., 2020 ). Considering the role of OJ on employee attitude and behavior, very few studies have explored the mediating role of work engagement (WE), a favourable employee attitude, in the association between organisational justice and OCB across the sectors ( Hassan et al., 2014 ; Yanthi and Rahyuda, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Organ (1977, 1997) theorized organizational citizenship behaviour mediates organizational justice (Cohen-Charash and Spector, 2001; Colquitt et al, 2001; Jafari and Bidarian, 2012; Knez et al, 2019; Wolfe and Lawson, 2020; Zayed et al, 2020). Following Zayed et al (2020: 448), we recognize five dimensions of organizational citizenship behaviour. While these tend to be studied in private organizations, we operationalize them for the public sector as they relate to inter-organizational justice (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Zayed et al (2020) found inter-organizational justice was a strong indicator for improving distributive outcomes (e.g. employee perceptions), suggesting a study of parole supervisory procedures is an effective way to explicate what officers believe about their work.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of bullying affect the organizational sustainability of higher educational institutions (Muazzam et al, 2020 ). Organizational sustainability is associated with how engaged/associated employees are with their work and organization (Glavas, 2012 ; Zayed et al, 2020 ). Activities that demoralize employees’ enthusiasm for the organization can negatively impact organizational sustainability and growth.…”
Section: Introductionmentioning
confidence: 99%